Aluminum Oxide Coatings as Nanoadsorbents for the Treatment of Effluents Colored with Eriochrome Black T - Kramer, Gustavo Raul (2025)
The contamination of water bodies with toxic compounds from the agricultural,industrial, and domestic sectors is a serious environmental problem. Adsorption is oneof the simplest, most functional, and economical methods for treating large volumes ofwater and removing its contaminant load. Thanks to its nanoporous structure, versatility,chemical inertness, and low-cost synthesis, anodic aluminum oxide (AAO) can be used asan adsorbent in a wide range of applications. In this work, nanostructured AAO coatingswere successfully synthesized, and their performance as adsorbents was evaluated indecolorization tests of Eriochrome Black T (EBT) solutions. The adsorption process wasfound to be dependent on the initial dye concentration, agitation, temperature, and contacttime. At 25 ◦C and 16 mg·L−1 initial EBT concentration, a maximum removal efficiency(%R) of 78% was obtained after 4.5 h at 500 rpm and after 5.5 h at 100 rpm, while withoutagitation, after 8.3 h of treatment, the highest %R was 40%. Furthermore, the adsorptionrate increased significantly with temperature, reaching a %R of 99% after 2.25 h at 60 ◦Cand 500 rpm. Additionally, it was demonstrated that the adsorbent can be used up to fourtimes with a removal efficiency greater than 50%.